Problems and Solutions - Nieto, José; Tipe, Jorge (Universidad Antonio Nariño, 2023)
The goal of this section is to present interesting mathematical problems and its solutions. We invite the readers to propose problems which may be tackled by high school or college students without specialized knowledge. Problem proposals and solutions should be e-mailed to the editors in English, Spanish or Portuguese. Proposals should be accompanied by a solution or, at least, enough information on why a solution is likely. Known open problems are not suitable.